Anxiety and Coping Strategies of Married Women - Rahman, Abdur; Bairagi, Arunavo; Dey, Biplob Kumar; Sultana, Aklima (Chittagong University Journal of Biological Sciences, 2024)
The present study attempted an empirical investigation to explore· the anxiety and coping strategies of married women according to their ' family type and' employment status in Chittagong city. A total of 100 respondents constituted the sample of ·the study. The Benga1i version of Anxiety scale developed by (Deeba and Begum 2004) and the Bengali version of Coping Scale adapted by Huque (2004) were used to measure anxiety and coping strategies of the respondents. Data were analyzed 'by using mean, standard deviation, two-way analysis of variance (ANOVA),). Pearson Product Moment Correlation and frequency. The findings of the present study showed' that family type has n·o significant effect on anxiety but employment. status has significant effect on anxiety (F=4.773, df= l.96, p<0.5). Housewives expressed 'more anxiety than employed married women. Result also showed that employment status and family type have significant effect on both problem-focus and emotion-focused coping. Anxiety was positively correlated with both problem-focused and emotion-focused coping. 47 participants were found mildly anxious, 16 were found moderately anxious, and 7 were found severely anxious, and 7 were found profoundly anxious. The Chittagong Univ. J.B. Sci..8(1&2): 63-74; 2013